Human papillomavirus and Epstein-Barr virus infection, p53 expression, and cellular proliferation in laryngeal carcinoma - Oliveira, Deilson Elgui de [UNESP]; Bacchi, Maura M.; Macarenco, Ricardo S.S. [UNESP]; Tagliarini, José Vicente [UNESP]; Cordeiro, Ricardo C.; Bacchi, Carlos E. (Oxford University Press (OUP), 2006)
Laryngeal carcinomas are aggressive neoplasms with controversial association with the human papillomavirus (HPV) and Epstein-Barr virus (EBV). So far, the impairment of p53 protein function and its impact on cellular proliferation has not been studied adequately in these tumors. In this work, molecular biologic techniques were used to assess the frequency of HPV and EBV in 110 squamous cell carcinomas of the larynx. In addition, accumulation of p53 and Ki-67 cell proliferation antigen expression in malignant cells was assessed by immunohistochemical analysis. High-grade HPV was found in 37.3% of cases, and none had demonstrable EBV infection. Accumulation of p53 was found in 78.2% of the cases, and it was related to a high Ki-67 labeling index and higher histologic grade. The results demonstrate association of HPV with more than one third of laryngeal carcinomas studied, mainly glottic tumors. Tumors with increased cell proliferation were more frequently high grade, with p53 accumulation and lymph node metastasis. © American Society for Clinical Pathology.
Keywords: EBV; Epstein-Barr virus; HPV; Human papillomavirus; Laryngeal cancer; p53; Tumor growth fraction; Ki 67 antigen; protein p53; adult; aged; antigen expression; cancer cell; cancer grading; cell proliferation; controlled study; disease severity; Epstein Barr virus; female; histology; human; immunohistochemistry; labeling index; larynx carcinoma; larynx tumor; lymph node metastasis; major clinical study; male; molecular biology; nonhuman; priority journal; protein function; squamous cell carcinoma; tumor growth; tumor suppressor gene; virus infection; Wart virus; Adult; Aged; Aged, 80 and over; Carcinoma, Squamous Cell; Cell Proliferation; DNA, Neoplasm; DNA, Viral; Epstein-Barr Virus Infections; Female; Fluorescent Antibody Technique, Indirect; Herpesvirus 4, Human; Humans; Immunoenzyme Techniques; Ki-67 Antigen; Laryngeal Neoplasms; Larynx; Lymph Nodes; Lymphatic Metastasis; Male; Middle Aged; Papillomaviridae; Papillomavirus Infections; Retrospective Studies; Tumor Suppressor Protein p53